PRODUCTIVITY IMPROVEMENT THROUGH THE IMPLEMENTATION OF LEAN MANUFACTURING IN A MEDIUM-SIZED FURNITURE INDUSTRY: A CASE STUDY - Gazoli de Oliveira, Andre Luiz; Ribeiro da Rocha Junior, Walter (The South African Journal of Industrial Engineering, 2019)
Small and medium-sized enterprises (SMEs) are very important to national economies. In Brazil, the furniture sector has many SMEs that suffer from international competition, especially from Chinese companies. To reduce this difficulty, this study provides a case study of the partial implementation of lean manufacturing (LM) in a medium-sized furniture industry with the aim of increasing productivity. As a result, the company increased its productivity by 27 per cent in the drilling sector. In addition, the case study shows how to implement LM in a medium-sized furniture industry, demonstrating the need to adapt the system to companies outside the automobile sector.